Reversible Dihydrogen Activation and Hydride Transfer by a Uranium Nitride Complex. Issue 14 (5th March 2018) - Falcone, Marta; Poon, Lok Nga; Fadaei Tirani, Farzaneh; Mazzanti, Marinella
Abstract: Cleavage of dihydrogen is an important step in the industrial and enzymatic transformation of N2 into ammonia. The reversible cleavage of dihydrogen was achieved under mild conditions (room temperature and 1 atmosphere of H2 ) by the molecular uranium nitride complex, [Cs{U(OSi(O t Bu)3 )3 }2 (μ‐N)] 1, leading to a rare hydride–imide bridged diuranium(IV) complex, [Cs{U(OSi(O t Bu)3 )3 }2 (μ‐H)(μ‐NH)], 2 that slowly releases H2 under vacuum. This complex is highly reactive and quickly transfers hydride to acetonitrile and carbon dioxide at room temperature, affording the ketimide‐ and formate‐bridged U IV species [Cs{U(OSi(O t Bu)3 )3 }2 (μ‐NH)(μ‐CH3 CHN)], 3 and [Cs{U(OSi(O t Bu)3 )3 }2 (μ‐HCOO)(μ‐NHCOO)], 4 . Abstract : Breaking and building : A rare uranium hydride complex is formed by cooperative dihydrogen cleavage by a uranium nitride. Hydride addition to small molecules, such as carbon dioxide, is facilitated.